Abstracts of 29th International Conference „Information Society and University Studies“ IVUS2024 - Veitaitė, Ilona (Vilnius University Proceedings, 2024)
29th International Conference „Information Society and University Studies“ IVUS2024 is the continuation of the annual conference series organized in succession by three universities: Vilnius University Kaunas Faculty, Vytautas Magnus University and Kaunas University of Technology. The event was started in 1995. In 2017, the conference became an international event. For the reason of a long history of this conference, we left conference acronym according to it's Lithuanian title "Informacinė visuomenė ir universitetinės studijos" – IVUS.
Keywords: Information Society and University Studies; Information Systems and Databases; Smart Systems and Environments; Software Engineering; Artificial Intelligence and Knowledge Engineering; Formal and Mathematical methods; Information Technology Applications